2016
DOI: 10.1016/j.rppede.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the pneumococcal 10-valent vaccine on reducing hospitalization for community-acquired pneumonia in children

Abstract: Objective:To describe and analyze the occurrence of hospitalizations for community-acquired pneumonia in children before and after the pneumococcal 10-valent conjugate vaccine implementation into the National Immunization Program.Methods:This is an ecological study that includes records of children younger than one year old, vaccinated and not vaccinated with the pneumococcal 10-valent conjugate vaccine in the periods pre- and post-inclusion of the vaccine in the National Immunization Program in the area cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 18 publications
(13 reference statements)
1
20
0
3
Order By: Relevance
“…Similar results were found on a study that analyzed the hospitalization of children and adolescents for respiratory sicknesses in the city of Anápolis, GO, from which the greater median was during the fall (Silva, et al, 2016). An international study carried out with the objective of evaluating the pneumococcus's seasonal tendency suggested that those bacteria are less infectious when the weather conditions are hot and rainy, and their transmissibility is enhanced in colder and drier months (Numminen, et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results were found on a study that analyzed the hospitalization of children and adolescents for respiratory sicknesses in the city of Anápolis, GO, from which the greater median was during the fall (Silva, et al, 2016). An international study carried out with the objective of evaluating the pneumococcus's seasonal tendency suggested that those bacteria are less infectious when the weather conditions are hot and rainy, and their transmissibility is enhanced in colder and drier months (Numminen, et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…Pneumococcal disease is a relevant health condition in Brazil and studies have demonstrated that hospitalization rates can be considered for the monitoring of the impact of the immunization program, thus contributing for a continuously evaluated active surveillance of the profile and distribution of cases within our country (Silva, et al, 2016;Kupek & Vieira, 2016;Kupek & Vieira, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A doença, sobretudo de etiologia bacteriana, é responsável por 20-40% das internações apenas no continente americano e, no Brasil, no ano de 2004 e 2006, as doenças pneumocócicas foram responsáveis por cerca de 34.000 internações, justificando de forma contundente, a importância da cobertura vacinal, como prevenção para internações hospitalares neste segmento etário. Portanto, apesar da alta taxa de crianças vacinadas neste estudo, uma pequena parcela não estava com a vacinação em dia, logo, estratégias assistenciais e gerenciais precisam ser empregadas para aumentar a cobertura vacinal no município, o que contribuirá para a redução de agravos evitáveis na infância 22 .…”
Section: Discussionunclassified
“…Of the studies summarized in Table 3 , three [ 32 34 ] did not seek to adjust for secular trends, potential biases and confounding. Seven addressed potential biases arising from changes in inpatient care by using all-cause hospitalizations as a denominator [ 35 37 ], analyzing control outcomes possibly with similar admission priority [ 20 , 31 , 35 ] or directly analyzing hospital capacity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%